Assessment of PGP traits of Bacillus cereus NDRMN001 and its influence on Cajanus cajan (L.) Millsp. phytoremediation potential on metal-polluted soil under controlled conditions - Narayanan, Mathiyazhagan; Pugazhendhi, Arivalagan; Ma, Ying (Frontiers in Plant Science, 2022)
The current study looked at the plant growth-promoting (PGP) traits of the pre-isolated and metal tolerant Bacillus cereus NDRMN001 as well as their stimulatory effect on the physiology, biomolecule content, and phytoremediation potential of Cajanus cajan (L.) Millsp. on metal polluted soil. The bauxite mine, which is surrounded by farmland (1 km away) has been severely polluted by metals such as Cd (31.24 ± 1.68), Zn (769.57 ± 3.46), Pb (326.85 ± 3.43), Mn (2519.6 ± 5.71), and Cr (302.34 ± 1.62 mg kg-1) that exceeded Indian standards. The metal tolerant B. cereus NDRMN001 had excellent PGP activities such as synthesis of hydrogen cyanide (HCN), siderophore, Indole Acetic Acid (IAA), N2 fixation, and P solubilisation. Furthermore, the optimal growth conditions (temperature of 30ºC, pH 6.5, 6% glucose, 9% tryptophan, and 1.5% tricalcium phosphate) for effective synthesis and expression of PGP traits in B. cereus NDRMN001 were determined. Such metal tolerant B. cereus NDRMN001 traits can significantly reduce metals in polluted soil and their PGP traits significantly improve plant growth in polluted soil. Hence, this strain (B. cereus NDRMN001) significantly improved the growth and phytoremediation potential of Cajanus cajan (L.) Millsp on metal polluted soil without (study I: 2 kg of sieved and autoclaved metal polluted soil seeded with bacterium-free C. cajan (L.) Millsp. seeds) and with (study II: 2 kg of sieved and autoclaved metal polluted soil seeded with B. cereus NDRMN001 coated C. cajan (L.) Millsp. seeds) with B. cereus NDRMN001 amalgamation. Fertile soil was used as control. The physiological parameters, biomolecule contents, and the phytoremediation (Cr: 7.74, Cd: 12.15, Zn: 16.72, Pb: 11.47, and Mn: 14.52 mg g-1) potential of C. cajan (L.) Millsp. were significantly effective in study II due to the metal solubilizing and PGP traits of B. cereus NDRMN001. These results conclude that the test bacteria B. cereus NDRMN001 considerably improved the phytoremediation competence of C. cajan (L.) Millsp. on metal polluted soil in a greenhouse study.